Ether lipid biosynthesis: isolation and molecular characterization of human dihydroxyacetonephosphate acyltransferase - Thai, Thanh-Phuong; Heid, Hans; Rackwitz, Hans-Richard; Hunziker, Andreas; Gorgas, Karin; Just, Wilhelm W. (FEBS letters, 1997)
In this paper we describe isolation and molecular characterization of human dihydroxyacetonephosphate acyltransferase (DAP-AT). The enzyme was extracted from rabbit Harderian gland peroxisomes and isolated as a trimeric complex by sucrose density gradient centrifugation. From peptide sequences matching EST-clones were obtained which allowed cloning and sequencing of the cDNA from a human cDNA library. The nucleotide-derived amino acid sequence revealed a protein consisting of 680 amino acid residues of molecular mass 77 187 containing a C-terminal type 1 peroxisomal targeting signal. Monospecific antibodies raised against this polypeptide efficiently immunoprecipitated DAP-AT activity from solubilized peroxisomal preparations, thus demonstrating that the cloned cDNA codes for DAP-AT.
Gesehen am 22.04.2025